Exam Question Management System using Cryptographic Technique / Tan Shu Pei - Tan, Shu Pei (2006)
Now days, with advance of technology, most of the instructor using computer to create the exam and test paper. And the created files are just simply store in the particular lecturer's computer without any secure protection towards the files. This will lead to the disclosure of confidential data such as the exam question if there is any unauthorized users hack into the system and steal the file. As such, this is why Exam Question Management System (EQMS) comes in to bring a more secure environment to store all the exam questions.Basically, EQM system is web-based system. Tl_lls system provides a secure database to ease the staff in managing the exam, test and tutorial question while maintaining high security. This system also provides a feasible environment for lecturer to create, share and manage the exam question with more effective and efficiently. With this system, lecturer will be able to create, edit, view, and delete the question and paper. The paper created also can be shared among lecturer. Nevertheless, the capability of lecturer to access to particular course is restricted.Lecturer are only allow to access to designated course.